Raw EK80 echosounder narrowband data collected during RV Meteor cruise extquotesingleAssessing Oceanic Impacts on Arrival and Transport of European Eel Larvae extquotesingle (M185) in 2022 - Roland Proud; Alix Claire Maria Rommel (PANGAEA, 2025)
These data consist of both underway and station-based echosounder observations collected during the 2022 M185 (Assessing Oceanic Impacts on Arrival and Transport of European Eel Larvae) cruise (29th October 2022 to the 26th November 2022) on the RV Meteor. Narrowband (38 and 200 kHz) underway acoustic data were collected continuously using a Simrad EK80 echosounder system (Kongsberg ES38-18/200-18C combined transducer and Simrad WBT Mini transceiver). The recording depth for the 2 frequencies was 1200 m, but the useful observation range (based on signal-to-noise ratios) was 1000 m and 200 m for the 38 and 200 kHz echosounders respectively. A calibration was carried out on the 17th November 2022, but the results (as assessed by the model RMS value) were deemed to be poor and were not used.